Influence of Repeated Injection Molding Processing on Some Mechanical and Thermal Properties of Wood Plastic Composites - Alperen Kaymakci; Nadir Ayrilmis (BioResources, 2016)
The influence of repeated cycles of injection molding on some mechanical and thermal properties of wood plastic composites (WPCs) was investigated. Pine wood flour (50 wt%) was mixed with HDPE (50 wt%) containing compatibilizing agent (MAPE, 3 wt%) in a co-rotating twin-screw extruder. The test specimens were produced by injection molding from the pellets dried to the moisture content (MC) of 1%. After the mechanical properties of the WPC test specimens were determined, the failed specimens were subsequently pelletized. These pellets were stored and dried for 4 to 6 h until the repeated injection was molded. These processes were repeated seven times. The results revealed that the flexural strength of WPCs increased by about 5.26% from the original granules to the third injection cycle, but further increments in the number of cycles decreased the flexural strength. The tensile strength and tensile modulus of the WPC specimens increased until the third cycle of injection molding while they tended to decrease after the third injection cycle.
Keywords: Thermal properties; Repeated injection molding; Tensile properties; Flexural properties; WPC; TP248.13-248.65; Biotechnology